2018
DOI: 10.3390/s19010035
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Wheat Yellow Rust Using Optimal Three-Band Spectral Indices in Different Growth Stages

Abstract: Yellow rust, a widely known destructive wheat disease, affects wheat quality and causes large economic losses in wheat production. Hyperspectral remote sensing has shown potential for the detection of plant disease. This study aimed to analyze the spectral reflectance of the wheat canopy in the range of 350–1000 nm and to develop optimal spectral indices to detect yellow rust disease in wheat at different growth stages. The sensitive wavebands of healthy and infected wheat were located in the range 460–720 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 50 publications
4
60
0
Order By: Relevance
“…This effect has been previously described for various patho-systems (e.g. Yu et al, 2018;Zhang et al, 2012;Zheng et al, 2019).…”
Section: Selected Spectral Indices and Resulting Spectral-temporal Fesupporting
confidence: 55%
See 2 more Smart Citations
“…This effect has been previously described for various patho-systems (e.g. Yu et al, 2018;Zhang et al, 2012;Zheng et al, 2019).…”
Section: Selected Spectral Indices and Resulting Spectral-temporal Fesupporting
confidence: 55%
“…context specificity). This problem has previously been described in detail with regard to growth stages of the crop, different phases in the pathogenesis and the presence of other stresses (Devadas et al, 2015;Zhang et al, 2012;Zheng et al, 2019).…”
Section: Limitations Of Time-point Specific Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, various field measurements on the ground canopy scale of cereal crops have focused on the detection of biotrophic diseases such as yellow rust [3,10,13,[23][24][25], brown rust [18,26], and powdery mildew of wheat [19]. This might be due to the fact that biotrophic diseases are more likely to appear on the upper leaf layers because of wind distribution and a preference for fresh and healthy leaf tissue [27].…”
Section: Of 20mentioning
confidence: 99%
“…Less important was the NIR wavebands > 800 nm and the red part of the spectrum. Various works have shown that VIs using wavelengths out of these spectral regions can be successfully used to detect rust diseases of wheat [17,18,25], or even for necrotrophic diseases of other crop plants such as groundnuts [42]. In the literature, it has been described that pigments and water influence the absorbance and reflectance of light with plant interactions [43][44][45].…”
Section: Ground Scalementioning
confidence: 99%